2019
DOI: 10.1002/pro.3679
|View full text |Cite
|
Sign up to set email alerts
|

The predominant roles of the sequence periodicity in the self‐assembly of collagen‐mimetic mini‐fibrils

Abstract: Collagen fibrils represent a unique case of protein folding and self‐association. We have recently successfully developed triple‐helical peptides that can further self‐assemble into collagen‐mimetic mini‐fibrils. The 35 nm axially repeating structure of the mini‐fibrils, which is designated the d ‐period, is highly reminiscent of the well‐known 67 nm D ‐period of native collagens when examined using TEM and atomic force spectroscopy. We postulate that it is the pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 45 publications
(109 reference statements)
1
20
0
Order By: Relevance
“…In another peptide, peptide Col108rr, the sequences in each of the three SUs of Col108 were shuffled such that while the amino acid composition of this peptide was the same as Col108, the sequence periodicity was lost. As expected, the Col108rr only formed non-specific aggregates [ 170 ];…”
Section: The Recombinant Collagen Peptidessupporting
confidence: 59%
See 2 more Smart Citations
“…In another peptide, peptide Col108rr, the sequences in each of the three SUs of Col108 were shuffled such that while the amino acid composition of this peptide was the same as Col108, the sequence periodicity was lost. As expected, the Col108rr only formed non-specific aggregates [ 170 ];…”
Section: The Recombinant Collagen Peptidessupporting
confidence: 59%
“…In another peptide, peptide Col108rr, the sequences in each of the three SUs of Col108 were shuffled such that while the amino acid composition of this peptide was the same as Col108, the sequence periodicity was lost. As expected, the Col108rr only formed non-specific aggregates [ 170 ]; In a new peptide, peptide Col877, the SU of Col108 was replaced by another 123 residues containing residues 877–986 of the α1 chain of human type I collagen [ 170 ] Thus, in contrast to Col108rr, Col877 had a very different amino acid composition from that of Col108, but had the same 123-residue sequence periodicity in its primary structure. Remarkably, Col877 can form mini-fibrils with the same 35-nm d -period as Col108.…”
Section: The Recombinant Collagen Peptidesmentioning
confidence: 88%
See 1 more Smart Citation
“…Recent studies show advancements in collagen mimetic peptide design, which has succeeded in obtaining collagen-mimetic trimers that are capable of self-assembly into periodic mini-fibers (44)(45)(46)(47). In these cases, sequence design is based on the selection of a fragment of a collagen helix, which is subsequently repeated in tandem (44)(45)(46)(47). Chen et al (45) have produced three collagen-mimetic helical peptides, two of which (designated by the authors as COL108 and COL877) have been shown experimentally to self-assemble into periodic structures.…”
Section: Collagen Model Peptidesmentioning
confidence: 99%
“…Nevertheless, the fact that the staggered assembly is also found for collagen-I in-vitro (albeit not the same as in-vivo) does indicate that it is indeed encoded to some extent in the primary sequence. Further evidence in this direction also comes from studies on the assembly of engineered concatemers of (non-hydroxylated) fragments of collagen-I sequences, that form staggered fibrils, but with different gap sizes than natural collagen-I fibrils [11][12][13].…”
Section: Introductionmentioning
confidence: 99%